Credit Constraints, Sector Informality and Firm Investments: Evidence from a Panel of Uruguayan Firms - Nestor Gandelman; Alejandro Rasteletti (Inter-American Development Bank (IDB), 2013)
This paper explores whether the extent of informality in a sector affects a firm's investment decision directly or indirectly through a credit availability channel. The dataset used in the estimation of the econometric models consists of an unbalanced panel of Uruguayan firms for the period 1997-2008. The results suggest that financial restrictions affect investment decisions in Uruguay, as an increase in credit to the private sector translates into higher investment rates. A one percentage point increase in overall credit growth translates into a one half percent increase in investment rates. It is also found that, although there is no direct effect of informality on the firm investment decision, there is an indirect effect through the borrowing channel. More specifically, financial restrictions reduce the amount of investment undertaken by Uruguayan firms, the effect being smaller if the firm operates in a sector with lower informality.
Keywords: E26; G21; O16; O4; 330